A Digital Model of Full-Cycle Training Based on the Zettelkasten and Interval Repetition System - Gevorg T. Malashenko; Mikhail E. Kosov; Svetlana V. Frumina; Olga A. Grishina; Roman A. Alandarov; Vadim V. Ponkratov; Tatyana A. Bloshenko; Lola D. Sanginova; Svetlana S. Dzusova; Munther F. Hasan (Emerging Science Journal, 2023)
The study aims to propose and validate a new digital model based on the Zettelkasten and interval repetition system for comprehensive and full-cycle training of the students. The core idea is to enhance the learning experience and effectiveness of the given training course by enhancing the student's attention during the learning and long-term information retention. In pursuit of the aforementioned research aim, the study incorporates a quantitative research methodology by combining experiments and a survey. In particular, the effectiveness of the proposed model was assessed via an achievement assessment involving two groups of students and assessing their scores on the same test. This was followed by a metacognitive awareness survey of the two groups to investigate their perceived understanding and performance (with and without the use of a model). The proposed model was found to be effective in enhancing the learning experience and effectiveness of the students on the training course. The Zettelkasten facilitates the management of the student's attention, while the interval repetition system contributes to increased retention. The students that used this model in their learning and preparation scored better than their peers. Also, they reported a significantly higher understanding and awareness of their learning than their peers. The model can be incorporated into the learning process or the provision of training courses to the students. This study is the first to suggest the integration of Zettelkasten and the interval repetition system into one learning model for the students. The article proposes a practical model that can be incorporated by teachers to improve the learning effectiveness of their students. This article has some limitations as well that must be acknowledged. Doi: 10.28991/ESJ-2023-SIED2-01 Full Text: PDF